PRAXIS AND THEORY OF ENVIRONMENTAL MARXISM - Dagmang, Ferdinand D. (Journal of Dharma, 2014)
Ecological Marxism is distinct from the environ-mentalists whose main focus is on the wrongness of anthropocentrism. Even with their diverse approaches, the latter have produced a common portrayal of the autonomy or integrity of nature. Thus, their stress on the debunking of the centrality of human beings eventually emphasized on the gaining of new ways of understanding nature. Ecological Marxism, however, followed Marx’s critique of capitalist production and accumulation. As could be expected, the eco-Marxists will no longer just propose a new way of understanding nature, but also a new praxis in dealing with nature—one that stresses on human development as co-evolving with nature. This environmental praxis which takes a socialist-economics turn, has followed a leftist (Red) course but may also have arrived at the intersection of the Green Movement. Through this, the ecological praxis and theory of Marx and his partner, Engels, has come to the fore.